A possibilidade de reconhecimento jurídico da união estável nas relações poliafetivas: uma análise a partir da filosofia do direito em hart - Freitas, Franciel Bonfim (Universidade Federal Rural do Semi-Árido, 2017)
The article deals with poliafetive unions, making an analysis on the possibility of legal recognition of these relations. Contrary and favorable arguments were presented for the officialization of poliafetive unions by the Brazilian extra-judicial service. The main discussion revolves around the validity of the Declaratory Public Declarations of Poliafetive Unions. It is intended to analyze the possibility of this recognition in the light of Hart's philosophy of law. It is a bibliographical and documentary research, based mainly on the systematic analysis of the works of the reference author. Rhetoric was used as an epistemological reference; As approach angle of the legal phenomenon. It is concluded that, due of the principle of freedom, individuals can constitute a poliafetive relationship, and there should be no impediment in the formalization of stable poliafetive union. In light of the theoretical reference of the research, one must prevail the will of the contractors to carry out the declaratory public deed of poliafetive union.
Keywords: União estável poliafetiva; Poliamor; Reconhecimento jurídico; Direito e moral; Stable poliafetive union; Polyamory; Legal recognition; Right and moral; CIENCIAS SOCIAIS APLICADAS::DIREITO